Nitinikiau innusi I keep the land alive - Penashue, Tshaukuesh Elizabeth 1944- (Contemporary studies on the North, 2019)
"Labrador Innu cultural and environmental activist Tshaukuesh Elizabeth Penashue is well-known both within and far beyond the Innu Nation. The recipient of a National Aboriginal Achievement Award and an honorary doctorate from Memorial University, she has been a subject of documentary films, books, and numerous articles. She led the Innu campaign against NATO's low-level flying and bomb testing on Innu land during the 1980s and '90s, and was a key respondent in a landmark legal case in which the judge held that the Innu had the "colour of right" to occupy the Canadian Forces base in Goose Bay, Labrador. Over the past twenty years she has led walks and canoe trips in nutshimit, "on the land," to teach people about Innu culture and knowledge. Nitinikiau Innusi: I Keep the Land Alive began as a diary written in Innu-aimun, in which Tshaukuesh recorded day-to-day experiences, court appearances, and interviews with reporters. Tshaukuesh has always had a strong sense of the importance of documenting what was happening to the Innu and their land. She also found keeping a diary therapeutic, and her writing evolved from brief notes into a detailed account of her own life and reflections on Innu land, culture, politics, and history. Beautifully illustrated, this work contains numerous images by professional photographers and journalists as well as archival photographs and others from Tshaukuesh's own collection. "Tshaukuesh's diary is sad, funny, resolute, eloquent, and real. Anyone interested in Innu traditional life and the struggle of the Innu today will want to read about the life of an Innu woman who fights for her people and the land, and who never, ever gives up." Julie Rak, Professor, Department of English and Film Studies, University of Alberta."--